PENGARUH BEBAN KERJA, STRES KERJA DAN PERCEIVED FAIRNESS TERHADAP BURNOUT PADA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN PADANG PARIAMAN - Restu Ramadani; Surya Dharma; Purbo Jadmiko (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
This study aims to prove and analyze the effect of workload, work stress and perceived fairness on burnout on BKPSDM employees in Padang Pariaman Regency. The sample size used is 50 employees and is a total of all employees of the BKPSDM Office in Padang Pariaman Regency. The analytical method used to prove the hypothesis is using multiple regression and t-statistical testing. Based on the results of hypothesis testing that has been done it was found that workload has a positive effect on burnout perceived by employees of the BKPSDM Office in Padang Pariaman Regency, while work stress and perceived fairness do not significantly influence the burnout felt by employees of the BKPSDM Office in Padang Regency.